393 Awardee Talk: Effect of trace mineral source on rumen fermentation and trace mineral distribution in the rumen. (30th November 2020) - Engle, Terry E
Abstract: The role that Cu and Zn play in rumen microbial fermentation is not well understood. Microorganisms use small proportions of dietary Cu and Zn for catalytic, structural, and stabilizing functions. In order for microorganisms to acquire Cu and Zn, the elements must be soluble in the rumen environment. Data would indicate that practical diets fed to ruminants without Cu and Zn supplementation are able to meet the microbial Cu and Zn requirements. Therefore, rumen solubility of supplemental Cu and Zn can impact rumen microbial fermentation characteristics. Numerous factors can impact rumen solubility of minerals, such as the pH of the rumen, the concentration of dietary antagonists (Mo, Fe, S, fiber, etc.), and mineral source. Earlier research has indicated that high soluble concentrations of Cu and Zn in the rumen environment can become toxic to certain rumen microorganisms and decrease fiber digestion. Recent research from our laboratory has indicated that hydroxy trace mineral (HTM) forms of Cu and Zn are relatively insoluble in the rumen and that a greater proportion of HTM remained loosely bound to the insoluble fraction within the rumen when compared to sulfate trace mineral (STM) sources of Cu and Zn. We have also reported that supplemental sources of Cu and Zn that are highly soluble in the rumen environment (STM) can decrease fiber digestion, reduce total VFA concentrations, and can become more tightly bound to rumen solid digesta than HTM sources of Cu and Zn. The stronger binding of STM relative to HTM to the solid rumen digesta fraction may reduce absorption in the small intestine. Future research investigating the flow and passage rate of different trace mineral sources through the abomasum into the duodenum and duodenal absorption efficiency of Cu and Zn from different TM sources is needed.